Historical basis of the theory of post-industrialism (Economics and region, 2022)
The article examines the evolution of the theory of post-industrialism in the context of the analysis of approaches to determining the stage of social development following the industrial (capitalist, bourgeois) stage. It has been established that, against the background of a large number of versions of the name of the stage of the development of society, which follows the industrial one, there is no established definition of it in the scientific literature. Currently, there are many interpretations of this newest era, depending on the criterion that is taken as the basis of the analysis: it is a post-industrial society, information society, information economy, new economy, knowledge economy, the economy of needs, etc. Such a variety of names indicates the absence of a unified approach to the analysis of the process of the formation and development of a new society. It requires a deeper theoretical understanding because the definition of the essence, characteristics, and forms of manifestation of a new stage of social development opens up prospects for a deeper understanding of its features as an environment where the entire complex social-economic relations of society. It has been proven that the most logical and optimal name for the society following the industrial one would be the term "post-industrial society" since the existing theories of the new society develop within one direction - post-industrialism as a theory describing the development of society at the stage following the industrial society. Unlike other approaches that consider the new era in opposition to other forms of management, which emphasize the revolutionary nature of social transformations, the concept of post-industrialism lacks such categoricalness and thinks of the new society as a logical continuation of the industrial era, as a new stage of social evolution.
Keywords: industrial society; post-industrialism; post-industrial society; post-industrial economy; socio-economic development of society